Empowerment of Aisyiyah kindergarten teachers in early detection of tuberculosis - Rohimi Zamzam; Erni Rita; Dewi Purnamawati; Azmi Al-Bahij (Universitas Muhammadiyah Magelang, 2021)
The increase in tuberculosis incidence in adults has implications for the increase in cases of tuberculosis in children. Tuberculosis in children has a long-term effect on the growth and development of children so that early prevention efforts are needed. Kindergarten school teachers are the closest people after parents who have an important role in early detection of tuberculosis in children. This activity aims to empower kindergarten school teachers in conducting early detection of tuberculosis in school children through health education activities. This activity was carried out on August 18-19, 2020 virtually, with lecture, discussion and simulation techniques, and was attended by 79 Aisyiyah Kindergarten teachers in DKI Jakarta. The evaluation results show that the average value of the pretest was 57.78 and the average value of the posttest was 72.02. Statistically, there is a significant difference in the average knowledge value of participants before and after health education. In addition, 74% of participants felt that the material provided was very useful, but there were also those who felt that the network was constrained, such as voices that were not clear and echoed.